Energy Policy of the European Union: Challenges and Possible Development Paths - Dudin, Mihail Nikolaevich; Frolova, Ð•vgenia Ð•vgenevna; Sidorenko, Valentina Nikolaevna; Pogrebinskaya, Ekaterina Alexandrovna; Nikishina, Irina Vladimirovna (International Journal of Energy Economics and Policy, 2017)
Energy policy is an important part of economic, environmental, and overall public policy of each country. For a long time, energy policy is being one of the most significant issues of each state and depends on many factors, including the availability of fossil energy sources and the geographic location of the country, access to natural resources, as well as political relations between energy exporters and importers. The article aims at analyzing the views of foreign authors on the assessment of the energy policy in the European countries in the context of further diversification and security of fuel supply, energy market liberalization, and renewable energy development. The article discusses the current state of energy policy of the EU member countries. The main tenet of this policy is the requirement to resolve the problems existing in the energy sector to ensure energy security. The EU countries import more than half of all energy consumed, and reducing this dependence provides for the completion of the gas market liberalization, the deployment of low-carbon technologies, renewable energy development, as well as enhancement of energy efficiency and energy saving. The authors analyze the energy policies of France and Germany, which are leaders in European energy policy. Besides, the article presents historical analysis of changes in the EU energy policy vector, as well as the main provisions of the new energy strategy to resolve European energy security problem. The article is prepared based on the analysis of works of foreign and Russian authors including politicians, officials, and researchers, as well as analysts and experts in the energy industry. Keywords: EU, energy policy, energy security, fuel sources, energy efficiency, energy conservation, energy intensity. JEL classifications: Q40, Q43, Q49